2023
DOI: 10.1002/mas.21864
|View full text |Cite
|
Sign up to set email alerts
|

An update on multiplexed mass spectrometry‐based lysosomal storage disease diagnosis

Abstract: Lysosomal storage disorders (LSDs) are a type of inherited metabolic disorders in which biomolecules, accumulate as a specific substrate in lysosomes due to specific individual enzyme deficiencies. Despite the fact that LSDs are incurable, various approaches, including enzyme replacement therapy, hematopoietic stem cell transplantation, or gene therapy are now available. Therefore, a timely diagnosis is a critical initial step in patient treatment. The‐state‐of‐the‐art in LSD diagnostic uses, in the first stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…In order to improve the efficiency of LSD testing, and the potential adoption into Newborn Screening programmes, a number of multiplex assays have been reported that utilise mass spectrometry or digital microfluidics (DMF). 13 , 14 , 15 Whilst, mass spectrometry is an extremely versatile and sensitive technique, cost (the initial price and service contract), footprint, and the need for higher trained staff can limit its suitability for smaller highly specialised lysosomal enzyme laboratories. Consequently, DMF may be more acceptable to such centres.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the efficiency of LSD testing, and the potential adoption into Newborn Screening programmes, a number of multiplex assays have been reported that utilise mass spectrometry or digital microfluidics (DMF). 13 , 14 , 15 Whilst, mass spectrometry is an extremely versatile and sensitive technique, cost (the initial price and service contract), footprint, and the need for higher trained staff can limit its suitability for smaller highly specialised lysosomal enzyme laboratories. Consequently, DMF may be more acceptable to such centres.…”
Section: Introductionmentioning
confidence: 99%